2001
DOI: 10.1111/j.1745-6606.2001.tb00101.x
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Perceptions of Privacy and Security Risks for Online Shopping

Abstract: Government and industry organizations have declared information privacy and security to be major obstacles in the development of consumer‐related e‐commerce. Risk perceptions regarding Internet privacy and security have been identified as issues for both new and experienced users of Internet technology. This paper explores risk perceptions among consumers of varying levels of Internet experience and how these perceptions relate to online shopping activity. Findings provide evidence of hypothesized relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
605
4
17

Year Published

2002
2002
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 914 publications
(647 citation statements)
references
References 32 publications
(32 reference statements)
21
605
4
17
Order By: Relevance
“…Yet, privacy and security statements of categories of Web sites do show a positive correlation with consumers' likelihood to purchase from those categories of sites (Miyazaki and Fernandez, 2000). A later study provided support for the relationship between security concerns and a consumer's willingness to purchase online, but did not support a relationship between privacy concerns and the willingness to purchase online (Miyazaki and Fernandez, 2001). Adding to this complex relationship is the fact that privacy and security seals may not be well recognized by consumers.…”
Section: Privacy and Security Statements And Third Party Verificationmentioning
confidence: 99%
“…Yet, privacy and security statements of categories of Web sites do show a positive correlation with consumers' likelihood to purchase from those categories of sites (Miyazaki and Fernandez, 2000). A later study provided support for the relationship between security concerns and a consumer's willingness to purchase online, but did not support a relationship between privacy concerns and the willingness to purchase online (Miyazaki and Fernandez, 2001). Adding to this complex relationship is the fact that privacy and security seals may not be well recognized by consumers.…”
Section: Privacy and Security Statements And Third Party Verificationmentioning
confidence: 99%
“…Nonetheless, it is important to distinguish between information seeking and the actual purchasing of products online. Prior research has demonstrated that individuals are concerned with the safety and security of their online transactions [56,68,80]. It is therefore plausible that although individuals find the Internet to be a more convenient and complete resource for product information than other media, such as newspapers and magazines, they may still feel uncomfortable buying products online.…”
mentioning
confidence: 94%
“…According to Miyazaki and Fernandez (2001), information security is widely recognized as a crucial by both government and industry organizations. From the consumer's perspective, information security issues can be a barrier to the growth of e-commerce.…”
Section: Information Securitymentioning
confidence: 99%